Al-Rasāil Al-Da’wiyah Al-Mustakhrojah Min Kitāb Al-Tafsīr Marāh Labīd Li-Syaikh Muhammad Nawāwī Al-Jāwī (Tahlīl Sūrah Āli Imrān Al-Āyah 104-105) : الرسائل الدعوية المستخرجة من كتاب التفسير مراح لبيد للشيخ محمد نووي الجاوي (تحليل سورة آل عمران الآية 104-105) - Firdaus, Rizal; Ahmadi, Andri; Hanif, Nazarudin; Al Madzali, Muhammad Yusri (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
This study aims to analyze the values of da'wah according to Syeh Nawawi Al-Jawī, especially in Surah Ali-Imran verses 104-105. The research method used in this study is a qualitative method. The source of the data is taken from the book of tafsir Marāh Labīd by Syeh Nawawi Al-Jawī, especially in the interpretation of Surah Ali-Imran verses 104-105, as well as several other references that are relevant to the study. The data collection technique uses document analysis, and the data analysis technique uses descriptive analysis techniques. The results of the study show that the da'wah messages contained in the book of tafsir Maraq Labīd by Shaykh Muhammad Nawawi in Surah Al-Imran verses 104-105 are four messages: da'wah to goodness (tauhid), amar ma'ruf nahi munkar, Motivation and Encouragement, Unity and Cooperation between da'i, menace. The implication of this study is that the da'i always prioritize the values of goodness (tauhid), amar ma'ruf nahi munkar, unity and cooperation between da'I in da'wah, as well as utilizing the targib and tarhib methods in their da'wah.